2015
DOI: 10.1097/md.0000000000002266
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Preoperative Circulating Monocyte Count in Patients With Breast Cancer

Abstract: Growing evidence showed that inflammation response plays an important role in cancer development and progression, and absolute lymphocyte count (ALC), absolute monocyte count (AMC), and lymphocyte to monocyte ratio (LMR) have been used as parameters of systemic inflammation in several tumors. In this study, we evaluated the prognostic significance of preoperative ALC, AMC and LMR in breast cancer and 2000 patients between January 2002 and December 2008 at Sun Yat-Sen University Cancer Center were enrolled. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 42 publications
6
25
0
Order By: Relevance
“…Furthermore, these prognostic implications were independent of the type of lymphoma again pointing towards mechanisms in the tumor environment and host immune response. This is consistent with several observations in patients with solid tumors, which revealed very similar prognostic implications of ALC and AMC in breast, gastric, pancreatic, nasopharyngeal, and non‐small cell lung cancer …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, these prognostic implications were independent of the type of lymphoma again pointing towards mechanisms in the tumor environment and host immune response. This is consistent with several observations in patients with solid tumors, which revealed very similar prognostic implications of ALC and AMC in breast, gastric, pancreatic, nasopharyngeal, and non‐small cell lung cancer …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the preoperative circulating monocyte level has also been identified as an independent risk factor for breast cancer-related death. Research has also reported that tumor-infiltrating T cells have the potential to stimulate monocyte to produce matrix metalloproteinase-2, matrix metalloproteinase-9, and vascular endothelial growth factor, which have significant roles in angiogenesis, invasion, and metastasis[33]. In contrast to the aforementioned systemic inflammatory response markers, lymphocytes are a major antitumor factor[34].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies have demonstrated the prognostic value of blood parameters and serum parameters, which are inexpensive, accurate, identified by easy method of detection and validated. Although underlying mechanism is unclear, increased pretreatment blood parameters and serum parameters have been confirmed to associate with prognosis of several cancers, such as neutrophil-to-lymphocyte ratio (NLR)17, 18, lymphocyte-to-monocyte ratio (LMR), monocyte count19, platelet-to-lymphocyte ratio (PLR)20, fibrinogen21 haptoglobin 22and C-reactive protein23. The serum levels of ALP and LDH are routine diagnostic tests in clinical laboratories.…”
Section: Discussionmentioning
confidence: 99%